Enhance Fluorescence Imaging and Remove Motion Artifacts by Combining Pixel Tracking, Interleaved Acquisition, and Temporal Gating - Christopher Mela; Francis Papay; Yang Liu (IEEE Photonics Journal)
Fluorescence imaging has been applied to improving many medical sub-specialties. In a clinical setting, there are motions of the imaging system and patients, as well as a high ambient light background. This presents a challenge for widely using fluorescence imaging systems clinically. In this paper, we present a novel approach combining computer vision and pulsed imaging system for enhanced fluorescence Imaging and motion artifacts removal. Specifically, we use a dense optical flow point tracking regime in conjunction with pulsed fluorescence excitation and interleaved acquisition. The system was characterized with respect to fluorescent detection sensitivity, using a clinically relevant fluorescent environment, and the results were compared to conventional steady-state (DC) fluorescence imaging. We also characterized the system with respect to fluorescence detection accuracy. We demonstrated a 45-fold reduction of motion artifacts by combining pixel tracking and fluorescence pixel identification with pulsed light imaging. Furthermore, the fluorescence imaging signal-to-background ratio is also improved for more than 2-fold. Our results indicate that pixel tracking, temporal gating, and interleaved acquisition can improve fluorescence imaging, especially for uses in realistic clinical settings where there is a high ambient light background.